Integrating technological innovation with Islamic leadership in hospital design: the role of visionary architectural consultants - Chaerina, Rina (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2024)
Technological advancements play a pivotal role in transforming hospital facilities, enhancing healthcare delivery and operational efficiency. However, the integration of these technologies must align with ethical principles, especially within the context of Islamic leadership values. This study explores how visionary architectural consultants can balance innovative technologies with Islamic principles of justice, integrity, and social welfare in hospital project transformation. A qualitative approach, including literature review, case studies, and interviews with experts, was used to analyze successful hospital projects integrating advanced technologies like HMIS, telemedicine, and sustainable design. Findings reveal that visionary consultants are essential in harmonizing technological advancements with Islamic values, creating healthcare environments that are both ethically grounded and technologically efficient. The study contributes to the growing body of knowledge by highlighting the role of ethical leadership in shaping hospital innovations and offers a holistic framework for future healthcare facility development.